Islamic Economic Actors: Comparative Study Of The Thinking Khurshid Ahmad And Monzer Khaf - Alif Mujiyana Eka Bella; Mugiyati (al-Afkar, Journal For Islamic Studies, 2024)
As Indonesian Muslims, we are also obliged to study economics as Muslim thinkers have done before us. Unfortunately, many Indonesian students still lack or have not studied economic concepts from an Islamic perspective or the economic principles developed by Islamic thinkers. Therefore, this article discusses two thoughts of Muslim figures in economic segmentation, namely the thoughts of Khurshid Ahmad and the thoughts of Monzer Khaf. Using the comparative literature study method, this research explores the thoughts and works of these two Islamic economic thinkers. The result of this research is that economics is an integral part of religion. By building Islamic-economic human resources, he makes humans as economic actors able to build Islamic economic civilization, especially in terms of consumption, so that it is in accordance with Islamic law and ethics.